Why and how NATO should adapt to a new Mediterranean security environment - Kasapoglu, Can (2019)
Abstract: NATO faces a problematic threat landscape in the Mediterranean. The Alliance has to deal with hot topics that range from Russia’s robust military posture and involvement in the Syrian Civil War to ISIS terrorism and the migrant crisis. To address all of these challenges, NATO should boost its engagement with partner nations, produce a new maritime security approach, and counterbalance Moscow’s strategic foothold in the eastern Mediterranean. (Autorenreferat)